2022
DOI: 10.7717/peerj.14580
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of flavonoids in Coreopsis tinctoria of different origins by UPLC–MS/MS

Abstract: To analyze the flavonoids in Coreopsis tinctoria and compare the differences in flavonoids among C. tinctoria of different origins, the chemical composition of C. tinctoria capitulum was analyzed by ultra-high-performance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS), and the flavonoid metabolites were analyzed and identified based on their retention time, mass-to-charge ratio and fragment ions in the UPLC-QTOF-MS matrix. Capitulum samples of C. tinctoria were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The advantage of the OPLS-DA model over PCA analysis is that it allows for maximum differentiation between the groups, thus facilitating the detection of differential metabolites [ 17 ]. Q 2 represents the predictive power of the model, and Q 2 > 0.9 is usually considered to indicate an excellent model [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of the OPLS-DA model over PCA analysis is that it allows for maximum differentiation between the groups, thus facilitating the detection of differential metabolites [ 17 ]. Q 2 represents the predictive power of the model, and Q 2 > 0.9 is usually considered to indicate an excellent model [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…To accurately screen for differential flavonoid metabolites between the aluminum stress treatment and control groups, a combination of fold change and variable importance in projection (VIP) values in the OPLS-DA model was utilized in our study to screen for differential flavonoid metabolites, according to the method described by Wang et al [ 17 ]. Differential flavonoid metabolites were selected according to the following criteria: significant fold change of ≥2 or ≤0.5, and VIP ≥ 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of 48 flavonoids, namely, 10 kaempferol, 1 apigenin and 3 catechin flavonoids, increased in Zhongzhe 1 sugarcane ( Figure 6 ). Previous studies have suggested that kaempferol [ 30 , 31 ], chalcone [ 32 ] and catechin [ 33 ] are bioactive substances that have antioxidant, antibacterial and antifungal properties. It has also been reported that endophytic fungi can cause the accumulation of flavonoids in the leaves of Cinnamomum longepaniculatum [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCA and PLA-DA were conducted to identify the SCMs, criteria of which were a fold-change (FC) ≥ 2 or ≤0.5 and VIP ≥ 1. PCA and PLS-DA were implemented in R software ( , accessed on 8 May 2021) to investigate variety-specific accumulation of metabolites in the leaves [ 30 , 54 ]. Finally, the SCMs between Zhongzhe 1 sugarcane and G160 sugarcane were analyzed via Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment.…”
Section: Methodsmentioning
confidence: 99%